Uji Daya Simpan Inokulum dan Ketahanan Lactobacillus plantarum terhadap pH Rendah sebagai Agensia Direct Fed Microbials untuk Ternak Ruminansia - H Suryani; D T Marya; D M Sinaga; N A Usman (Politeknik Negeri Lampung, 2023)
Direct Fed microbials (DFM) is a product of non-pathogenic live microorganisms that is beneficial when given to humans or livestock to improve livestock health, feed conversion efficiency and perfomance by suppressing pathogenic microorganisms in the digestive tract and influencing the balance of intestinal microbes. This study aims to provide information about the potential of Lactobacillus plantarum FNCC 0020 as a DFM agent. This study used a descriptive experimental method. Parameters observed included resistance tests to acid pH (5, 3, 2), pH 7 were also tested to determine resistance to neutral pH. The ability of Lactobacillus plantarum FNCC 0020 to survive at room temperature with different incubation times (5, 7, 10 days) were also tested to determine the storability of Lactobacillus plantarum FNCC 0020 inoculum at room temperature.. The results showed that Lactobacillus plantarum FNCC 0020 had resistance to the lowest pH (2) and also survived at neutral pH (7) with a total colony of 2.25 x 108 and .3 x 107 CFU mL-1, respectively. Lactobacillus plantarum FNCC 0020 inoculum can be stored at room temperature for up to 10 days and still has a total colony of 3.8 x 107 CFU mL-1.